PENGARUH KOMUNIKASI INTERPERSONAL TERHADAP KEKERASAN DALAM PACARAN SISWA SMK - Yuni Kurniasari; Umbu Tagela; Yustinus Windrawanto (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
The purpose of this study was to determine the significance of the influence of interpersonal communication on students dating violence in XII Tata Busana class of SMK PGRI 1 Salatiga. This type of research uses a causal comparative approach. The population of this research is students of XII Tata Busana class at SMK PGRI 1 Salatiga for the academic year 2022/2023 with a total of 40 students. The research sample was taken using total sampling technique. The data analysis technique used is simple linear regression technique with the help of the IBM SPSS Statistics 25.0 program. The results of this study indicate that there is a significant negative influence of interpersonal communication variables on students dating violence. These results are evidenced by the acquisition of a tcount value which has a negative sign of -2.408 and a significance value (p) of 0.021 <0.05 is obtained